BODIPY derivatives: design, synthesis, and evaluation as chemosensors, probes for bioimaging, and photosensitizers for PDT - Pinto, Sónia Catarina Silva (2022)
Dissertação de mestrado em Técnicas de Caracterização e Análise Química